2018
DOI: 10.21278/tof.42si104
|View full text |Cite
|
Sign up to set email alerts
|

Ground Thermal Response and Recovery after Heat Injection: Experimental Investigation

Abstract: SummaryMonitoring the ground thermal response to a constant heat flux input is common method for determination of effective ground properties needed for sizing the ground coupled heat pumps. In this work, the experimental procedure included two TRT's with different average injection heat fluxes, 4.43 kW and 7.64 kW, applied to the same borehole. Recorded temperatures of fluids, circulated in an experimental borehole heat exchanger U-tube, are used to determine the ground thermal conductivity and the borehole t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The ground thermal conductivity and borehole thermal resistance was determined by circulating heated fluid in a U-tube type BHE, while thermocouples placed on the borehole wall measured temperature profiles of undisrupted ground as well as during the recovery period. The analysis indicated that the true undisturbed state after rejected heat flux cannot be reached in short time while the use of higher rejection heat flux reduces the influence of the ground's inhomogeneity on the results obtained [4].…”
Section: Introduction and Literature Overviewmentioning
confidence: 94%
See 1 more Smart Citation
“…The ground thermal conductivity and borehole thermal resistance was determined by circulating heated fluid in a U-tube type BHE, while thermocouples placed on the borehole wall measured temperature profiles of undisrupted ground as well as during the recovery period. The analysis indicated that the true undisturbed state after rejected heat flux cannot be reached in short time while the use of higher rejection heat flux reduces the influence of the ground's inhomogeneity on the results obtained [4].…”
Section: Introduction and Literature Overviewmentioning
confidence: 94%
“…In order to evaluate the thermal response of heat rejection and recovery behaviour of the ground, two thermal response tests (TRT) were conducted on the same experimental borehole heat exchanger [4]. The testing consisted from two different heat pulses enforced to the same borehole, one with 4,43 kW and the other with 7,64 kW rejected heat flux.…”
Section: Introduction and Literature Overviewmentioning
confidence: 99%
“…In the last decade alone there has been a rise of research when it comes to optimizing the BHE system, by observing the influence of various geometrical settings, hydraulic settings and heat rates on the overall performance. Various studies have focused on a better understanding and more precise estimation of effective thermal conductivity and borehole thermal resistance [1][2][3][4] as important parameters when exploiting the shallow geothermal resource. Current methods of determining the average fluid temperature within BHE, as well as the influence of various measuring methods during TRT, on the final determination of thermal properties are also available [5][6][7].…”
Section: Introduction and Literature Overviewmentioning
confidence: 99%
“…The origin of both procedures lies in the same diffusivity differential equation, with solutions for heat conduction or pressure transient analysis during radial flow in porous media. The use of the step thermal response test showed that it is suitable when determining heat rejection/extraction rates, useful for design optimization of the BHE field [3,10]. The influence of the groundwater advection on the efficiency and modelling of the ground BHE is detailed, with the study of its relationship with the modeling of the BHE field [7,[11][12][13].…”
Section: Introduction and Literature Overviewmentioning
confidence: 99%